A STUDY OF STARTUPS’ EMPLOYEE RETENTION - Dr. Jayendrasinh Jadav (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2021)
It was India that first claimed the title of "nation" in the early twentieth century. After a significant increase in innovative startups and the beginning of this country, which is home to a new breed of youth startups, the Indian starting point has clearly developed to become the world's third largest form of technology startup since 2010. During the course of a year, the number of new businesses climbed by 40%, and it is predicted to reach 4,200 by the end of 2015. Trowner represents a significant financial burden on enterprises. Furthermore, it has a significant impact on the functioning of the organisation. High employee turnover also has a detrimental effect on the bottom line of the business. According to experts, it will cost twice as much as the pay of an employee to find and train a replacement for a lost post. Additionally, it can have a detrimental influence on the morale of existing employees, making it vital to understand the overall effectiveness of emphasising the necessity of turnover reduction. The purpose of this study is to better understand the consequences of startup companies that retain their staff.